Evaluación de tres abonos foliares orgánicos en el cultivo de chocho (Lupinus mutabilis BENTH), en la quinta experimental docente La Argelia - Astudillo Robles, Eliana Paola (2016)
With the aim of evaluating agricultural yields in crop chocho (Lupinus mutabilis) and diversify production thereof, the experiment was performed in the Quinta Experimental Docente “La Argelia” , using three foliar fertilizers in two doses AMINH2O-Gel 2.0 and 3 , 0 l / ha, Eco-Hum 1.0 and 1.5 l / ha and Kynester 0.5 and 1.0 l / ha, he applied every 20 days the payment taking into account the recommendations of the product label, it was planted in May and the harvest was made in the months of December to January. Yields exceeded those presented in the northern highlands of Ecuador obtaining higher production even witness. The best treatments with a higher agricultural yields achieved are: Kynester at doses of 1.0 l / ha, giving a yield of 1507 kg / ha; followed foliar fertilizer AMINH2O-Gel in doses of 3l / ha thus obtained a yield of 1498 kg / ha, also in an effort to diversify production two workshops were conducted in the experiment attended by farmers in the basin of Loja, teachers and students responding to inquiries from participants and providing seed to farmers who settled on planting this grain. Finally a radio transmission was in the program "La Hora del Agro with Aroma of Our Land" which airs on Radio Universitaria 98.5 on Saturdays from 05:00 to 06:00 and optimum pickup the day Sunday at the same hour, the program phone calls from people interested in the topic was received that expressed interest in planting this grain as they are marketed in processed form.